SARS-CoV-2: Origin, Evolution, and Targeting Inhibition - Ning, Shuo; Yu, Beiming; Wang, Yanfeng; Wang, Feng (Frontiers in Cellular and Infection Microbiology, 2021)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) emerged and quickly spread to all parts of the world. Nowadays, no specific drugs or antibodies that claimed to cure severe acute respiratory diseases. For SARS-CoV-2, the spike (S) protein recognizes and binds to the angiotensin converting enzyme 2 (ACE2) receptor, allowing viral RNA to enter the host cell. The main protease (Mpro) is involved in the proteolytic process for nonstructural protein mature, and RNA-dependent RNA polymerase (RdRp) is responsible for replicating the RNA genome. Due to the pivotal physiological roles in viral invading and replication, S protein, Mpro, RdRp are regarded as the main targets of SARS-CoV-2 treatment. In this review, we made an evolutionary analysis of SARS-CoV-2 with other mammals infected coronaviruses that have sprung up in the past few decades and described the pathogenic mechanism of SARS-CoV-2. We also displayed the structural details of S protein, Mpro, and RdRp, as well as their complex structures with different chemical inhibitors or antibodies. Structural comparisons showed that some neutralizing antibodies and small molecule inhibitors could better inhibit S protein, Mpro, or RdRp. Besides, we analyzed the structural differences between SARS-CoV-2 ancestral S protein and D614G mutant, which led to a new round of worldwide pandemic recently. Under this context, we outline the methods that might cure COVID-19 potentially and provide a summary of effective chemical molecules and neutralizing antibodies.